Effects of Slot Additions on the Aerodynamic Performance of NACA 4412 Airfoil at High Angles of Attack - Novi Indah Riani; Didik Sugiono; Yudi Hartono; Muhamad ‘Uzair (SINTEK JURNAL: Jurnal Ilmiah Teknik Mesin, 2025)
Stall is a critical phenomenon that adversely affects airfoil performance, particularly on aircraft wings, by causing a drastic reduction in lift. A lower stall angle is desirable as it allows the airfoil to maintain maximum lift over a broader range of angles of attack. One effective method for stall delay is the implementation of slots on the airfoil surface. This experimental study investigates the effects of slot additions on the aerodynamic performance of a NACA 4412 airfoil at high angles of attack. The experiments were conducted in a laboratory-scale wind tunnel at a flow velocity of 14 m/s, corresponding to a Reynolds number of 1.36 × 105. The angles of attack tested were α = 10°, 12°, 14°, 16°, and 18°. The results indicate that the maximum lift force of 5.418 N was achieved at α = 16°, while the minimum drag force of 0.0176 N was observed at α = 10°. The peak flow velocity in the wake, measured at 15.42 m/s, occurred at α = 18° at a dimensionless height of y/h = 0.90. The addition of slots effectively delayed the stall angle to 16°. This research contributes to the understanding of aerodynamic performance enhancement through flow control, offering valuable insights for the design of high-lift systems in aerospace applications.